2004
DOI: 10.1021/jm0498203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of Novel Histamine H1 Antagonists:  Indolylpiperidinyl Benzoic Acid Derivatives

Abstract: A series of indolylpiperidinyl derivatives were prepared and evaluated for their activity as histamine H(1) antagonists. Structure-activity relationship studies were directed toward improving in vivo activity and pharmacokinetic profile of our first lead (1). Substitution of fluorine in position 6 on the indolyl ring led to higher in vivo activity in the inhibition of histamine-induced cutaneous vascular permeability assay but lower selectivity toward 5HT(2) receptor. Extensive optimization was carried out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Coupling of compound 6 with known compound 12 would produce the desired target compound 2. Synthesis of compound 12 has been reported in the literature, through a sequence of coupling of 3-(3,4,5-trifluorophenyl)-acryloyl chloride (10) with piperidin-4-yl-acetic…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupling of compound 6 with known compound 12 would produce the desired target compound 2. Synthesis of compound 12 has been reported in the literature, through a sequence of coupling of 3-(3,4,5-trifluorophenyl)-acryloyl chloride (10) with piperidin-4-yl-acetic…”
Section: Resultsmentioning
confidence: 99%
“…4 These sequential procedures for the synthesis of compound 12 were modified for a better overall yield, by first brominating commercially available 4-ethoxycarbonylmethylpiperidine-1-carboxylic acid tert-butyl ester to give 4-(bromo-ethoxycarbonyl-methyl)-piperidine-1-carboxylic acid tert-butyl ester (7) 3 ; followed by the deprotection of the Boc group on compound 7 with TFA to afford bromopiperidin-4-yl-acetic acid ethyl ester (8). Compound 8 in the presence of triethylamine was then coupled with 3-(3,4,5-trifluoro-phenyl)-acryloyl chloride (10), which was prepared by treating 3-(3,4,5-trifluoro-phenyl)-acrylic acid (9) with SOCl 2 , to produce compound 11. Compound 11 was further hydrolyzed upon treatment with LiOH, followed by acidification with hydrochloric acid to give acid 12 in 98% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of piperidone with indole gave compound 9, which was converted to compound 10 via hydrogenation with Pd/C. 10 Compound 11 was synthesized from phthalimide by the same method as compound 8. Substitution of the methylsulfonyl group of piperidine with phthalimide potassium salt followed by the removal of the Boc group afforded the desired compound 12.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies should be addressed to SAR of inverse agonist activity of H 1 -antihistamines to understand the molecular mechanism how inverse agonists stabilize the inactive form of H1R. It was reported that some indolylpiperidines show H 1 -antagonistic activity [22]. Examination of their inverse agonist activity may provide some useful insights.…”
Section: Discussionmentioning
confidence: 99%